Laser vibrometry in the quality control of the break of tanned leather. (May 2018) - Preciado, J. Sanchez; Lopez, C. Perez; Hernandez-Montes, M. del Socorro; Torre-Ibarra, M. de la; Moreno, J.M. Flores; Ruiz, C. Tavera; Mendoza Santoyo, F.; Galan, M.
Highlights: Single point laser vibrometry as a noncontact and nondestructive optical method. Increase the effectiveness of leather classification for quality control in the tanning industry. Leather samples were classified according to their break level using their dynamical response to acoustic stimulation. Metrics that are applied in the classification of samples of leather according to five levels of quality. The analysis of an elastic material with a nondestructive method that is used to calculate the mechanical constants of leather by using modal analysis. Abstract: Tanning industry treats hides and the skin of animals for their use in products such as clothes, furniture and car's interiors. The worth of leather is highly affected by defects that may appear prior or during the tanning process. Break, which refers to the wrinkling of the grain surface of leather, is one of the main issues because it affects not only the visual appearance of leather, but also its mechanical properties. The standardized method to classify the break pattern is done by bending the leather with the hand and comparing visually the resulting wrinkles that appear with a reference pattern, which makes the classification subjective and limits the evaluation to small areas. Laser vibrometry is an optical technique that has been applied in vibrational and modal analysis, which are methodologies used to obtain the mechanical properties of materials. This work demonstrates the use of a single-point vibrometer as a noncontact and nondestructive optical method to discriminate among five break levels, which could increase the effectiveness of leather classification for quality control in the tanning industry.